Answer:
ummmmmmm is that the whole question cuz apearently im slow cuz i dont understand and im in 10th
Step-by-step explanation:
<span><span> Let ABC be an isosceles triangle with AB = AC. Let M denote the midpoint of BC (i.e., M is the point on BC for which MB = MC). Thena)<span> </span>Triangle ABM is congruent to triangle ACM.b)<span> </span>Angle ABC = Angle ACB (base angles are equal)c)<span> </span>Angle AMB = Angle AMC = right angle.d)<span> </span>Angle BAM = angle CAM
</span></span>
X= 38.12325882663022
First take SOHCAHTOA
We’ll use SOH.
SOH means sine(angle)=opposite/hypotenuse.
So sine(43 degrees)=26/X
Which means 26/(sine(43 degrees))=X
Which means 26/0.681998360062499=X
The elimination method works by adding the two equations and eliminating one variable. Then you solve an equation in one variable. Finally, you use substitution or elimination again to find the other variable. Sometimes, by simply adding the equations, a variable is not eliminated. Then you need to multiply one or both equations by a factor to get a variable to be eliminated.
A)
2x - 4y = 8
x + 3y = -11
Adding the equations does not eliminate x or y.
Notice that in the first equation, every coefficient is even. We can divide both sides of the first equation by 2. Then the first term would be x. Instead, let's divide both sides of the first equation by -2. Then the x's will be eliminated.
-x + 2y = -4 <-- The first equation divided by -2
x + 3y = -11 <-- The original second equation. Now we add the equations.
----------------
5y = -15
y = -3
Now that we know y = -3, we substitute it into the first original equation and solve for x.
2x - 4y = 8
2x - 4(-3) = 8
2x + 12 = 8
2x = -4
x = -2
Answer: x = -2; y = -3
B)
We see that the x's will be eliminated by addition. Just add the equations.
-3x + 7y = 9
3x - 7y = 1
---------------
0 + 0 = 10
0 = 10 <---- this is a false statement, so this system of equations has no solution.